2018
DOI: 10.21577/0103-5053.20180080
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Immunosensor Made with Antigenic Peptide NS5A‑1 Immobilized onto Silk Fibroin for Diagnosing Hepatitis C

Abstract: Immunosensors based on impedance spectroscopy for diagnosing hepatitis C are reported where the sensing units were made with the antigenic peptide PPLLESWKDPDYVPPWHG (NS5A-1) derived from the NS5A protein of the hepatitis C virus (HCV) immobilized in layer-by-layer (LbL) films with silk fibroin (SF) and deposited on gold interdigitated electrodes. The electrical response of the sensing units varied upon immersion into solutions containing the antibody anti-HCV owing to the biomolecular recognition of NS5A-1. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The virus is usually transmitted through exposure to the blood (transfusion or infected needles) of an infected individual (Alter, 2007). This brings the need for an effective, low‐cost sensor for the diagnosis of Hepatitis C. A biosensor, based on impedance spectroscopy, was fabricated by Lima et al (2018), which used antibody–antigen interaction for the detection of HCV, as demonstrated in Figure 6A. A specific antigenic peptide NS5A‐1 (from the NS5A protein) was immobilized in an SF film using the layer‐by‐layer (LbL) method.…”
Section: Application Of Silk Biomaterials In Biosensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The virus is usually transmitted through exposure to the blood (transfusion or infected needles) of an infected individual (Alter, 2007). This brings the need for an effective, low‐cost sensor for the diagnosis of Hepatitis C. A biosensor, based on impedance spectroscopy, was fabricated by Lima et al (2018), which used antibody–antigen interaction for the detection of HCV, as demonstrated in Figure 6A. A specific antigenic peptide NS5A‐1 (from the NS5A protein) was immobilized in an SF film using the layer‐by‐layer (LbL) method.…”
Section: Application Of Silk Biomaterials In Biosensorsmentioning
confidence: 99%
“…Therefore, the analyte used for the detection of the virus was antibody anti‐NS5A‐1 which is specific to the NS5A protein. This led to the development of a biosensor with high specificity and sensitivity that could detect anti‐HCV antibody concentration as low as 2 ng ml −1 with a linear detection range of 0−0.2 and 0−0.02 μg ml −1 for 1 and 5‐bilayer LbL films, respectively (Lima et al, 2018). In another similar attempt for the detection of HCV, luminescent YVO 4 :Eu 3+ nanoparticles were constructed by Lima et al (2016).…”
Section: Application Of Silk Biomaterials In Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…16,75 In this regard, fibroin has been extensively studied and stands out against other materials thanks to its unique properties, which include being mechanically robust 1,14,74 and transparent throughout the visible spectrum, presenting smooth surface and variable refractive index, [81][82][83] and being susceptible to physical changes in its structure. 76,77 All these characteristics allow the preparation of passive or active devices 75 based on pure fibroin 16 or fibroin in the presence of other components, 167 to provide materials like supports for electrodes, 16,221 lasers, [168][169][170][171][172][173][174] biosensors, [175][176][177][178][179][180] waveguide, 83,181,182 fuel cells, 183 and energy storage devices. 184 Kim and collaborators built an electrode consisting of a chip supported on an ultrathin and resorbable fibroin substrate.…”
Section: Electronic and Photonic Devicesmentioning
confidence: 99%
“…The evaluation of the dielectric constant of the nanostructured films allows the appropriate choice of materials that best suits a specific application. Besides, evaluating the charge density in the outermost layer of the film supports choosing molecules that maximize the adsorption of the active layer in biosensing, potentially increasing their sensitivity. …”
Section: Introductionmentioning
confidence: 99%